2019
DOI: 10.1109/access.2019.2945524
|View full text |Cite
|
Sign up to set email alerts
|

SISC: End-to-End Interpretable Discovery Radiomics-Driven Lung Cancer Prediction via Stacked Interpretable Sequencing Cells

Abstract: Lung cancer is the leading cause of cancer-related death worldwide. Computer-aided diagnosis (CAD) systems have shown significant promise in recent years for facilitating the effective detection and classification of abnormal lung nodules in computed tomography (CT) scans. While hand-engineered radiomic features have been traditionally used for lung cancer prediction, there have been significant recent successes achieving state-of-the-art results in the area of discovery radiomics. Here, radiomic sequencers co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Similar results were obtained by Lao et al., 60 who demonstrated that the deep features extracted via transfer learning performed better than radiomic features in prediction of overall survival in glioblastoma patients. However, DL models are still perceived as “black boxes,” meaning that it is difficult to determine how they arrive at their predictions, which impairs their use by clinicians as part of their clinical practice 61,62 . To address this issue, we searched for the radiomic features most related to the DL features in the DL CT,BED model.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained by Lao et al., 60 who demonstrated that the deep features extracted via transfer learning performed better than radiomic features in prediction of overall survival in glioblastoma patients. However, DL models are still perceived as “black boxes,” meaning that it is difficult to determine how they arrive at their predictions, which impairs their use by clinicians as part of their clinical practice 61,62 . To address this issue, we searched for the radiomic features most related to the DL features in the DL CT,BED model.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed architecture provided better insights into the model's decisions and achieved better performance compared to the considered approaches. The proposed radiomic sequencer achieved correct predictions that can potentially improve clinical adoption [182].…”
Section: Computed Tomography (Ct)mentioning
confidence: 90%
“…The results were incorporated to increase the radiologists' confidence level for clinical diagnosis [180]. A stacked interpretable architecture was proposed for the classification of abnormal lung nodules for lung cancer prediction on LIDC-IDRI dataset [182]. The proposed architecture provided better insights into the model's decisions and achieved better performance compared to the considered approaches.…”
Section: Computed Tomography (Ct)mentioning
confidence: 99%
“…By comparing it with three popular interpretability methods (CAM, VBP, and LRP), it was found that the proposed method can generate a more accurate and clear visual interpretation map. Similarly, the stacked interpretable sequencing cells (SISC) architecture was introduced [ 67 ] to predict lung cancer by generating attentive maps to provide explanations. It can not only achieve remarkable results for lung prediction but also highlight the crucial regions.…”
Section: Applications Of Interpretability Methods In Disease Diagnosismentioning
confidence: 99%